Effect of Feeding Hedge Lucerne (Desmanthus virgatus) on Milk Production and Milk Composition in Gir Cows - Karangiya, Vijay K; Parmar, Monika R; Chavda, Miteshkumar R; Ribadiya, Nilay K; Savsani, Harish H; Borkhatariya, Devasee N; Chavda, Jignesh A (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Present study was conducted on 18 lactating Gir cows selected after attaining peak yield to assess the effect of feeding different levels  of Hedge lucerne (Desmanthus virgatus) on milk production and milk composition. Cows were divided into three groups having six  animals in each group on the basis of body weight, daily milk yield and parity, and randomly allotted to three dietary treatments, i.e., T1 (control) routine feeding adopted at cattle breeding farm, T2 - 75% CP from concentrate and 25% CP from Hedge lucerne, and T3  - 50% CP from concentrate and 50% CP from Hedge lucerne. Overall dry matter intake (kg/day) was found non-significantly different  among treatment groups. Mean daily milk yield recorded over entire experimental period of 120 days was 7.48±0.92, 7.82±0.78 and  7.19±0.47 in T1, T2 and T3 groups, respectively, which did not differ statistically. Non-significant difference was also recorded in milk fat  (%). However, there was significant difference between groups in terms of lactose, protein and SNF content of milk. It might be due to  change in the ratio of concentrate: roughage in the diets of experimental animals.
Keywords: Cattle; Feeding; Gir; Hedge lucerne; Milk composition; Milk production